2021
DOI: 10.21203/rs.3.rs-184044/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective effect of Bmscs-derived exosomes on testicular ischemia-reperfusion injury in rats

Abstract: Background Testicular Ischemia reperfusion injury(IRI) is a major pathophysiological process of surgical reduction after testicular torsion, and oxidative stress is the main injury factor. However, the role of BMSCs-derived exosomes in testicular IRI and its mechanism have not been reported. In this study, we investigated the protective effect of bone marrow mesenchymal stem cell-derived exosomes against testicular ischemia-reperfusion injury. Methods Results: BMSCs were successfully isolated and cultured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Exo therapy at a single dose signi cantly improved in tissue repair via regulating Cis-induced autophagy. Previous studies have showed that exos protected against testicular ischemia/reperfusion injury in rats through antioxidant, anti-in ammatory, and antiapoptotic mechanisms (43,44). It has also been reported that antitumoural drugs trigger the autophagy process.…”
Section: Discussionmentioning
confidence: 98%
“…Exo therapy at a single dose signi cantly improved in tissue repair via regulating Cis-induced autophagy. Previous studies have showed that exos protected against testicular ischemia/reperfusion injury in rats through antioxidant, anti-in ammatory, and antiapoptotic mechanisms (43,44). It has also been reported that antitumoural drugs trigger the autophagy process.…”
Section: Discussionmentioning
confidence: 98%